In vivo synergistic activity of a CAZyme cassette from Acidothermus cellulolyticus significantly improves the cellulolytic activity of the C. bescii exoproteome. Issue 11 (3rd August 2017) - Kim, Sun‐Ki; Chung, Daehwan; Himmel, Michael E.; Bomble, Yannick J.; Westpheling, Janet
ABSTRACT: The use of microbial cells to convert plant biomass directly to fuels and chemicals is referred to as consolidated bioprocessing (CBP). Members of the bacterial genus, Caldicellulosiruptor (Gram‐positive, anaerobic hyperthermophiles) are capable of deconstructing plant biomass without enzymatic or chemical pretreatment. This is accomplished by the production and secretion of free, multi‐domain enzymes that outperform commercial enzyme cocktails on some substrates. Here, we show that the exoproteome of Caldicellulosiruptor bescii may be enhanced by the heterologous expression of enzymes from Acidothermus cellulolyticus that act synergistically to improve sugar release from complex substrates; as well as improve cell growth. In this work, co‐expression of the A. cellulolyticus Acel_0615 β‐glucanase (GH6 and GH12) and E1 endoglucanase (GH5) enzymes resulted in an increase in the activity of the exoproteome on Avicel; as well as an increase in growth of C. bescii on Avicel compared to the parental strain or the strain expressing the β‐glucanase alone. Our ability to engineer the composition and effectiveness of the exoproteome of these bacteria provides insight into the natural mechanism of plant cell wall deconstruction, as well as future directions for improving CBP. Biotechnol. Bioeng. 2017;114: 2474–2480. © 2017 Wiley Periodicals, Inc. Abstract : Members of the bacterial genus, Caldicellulosiruptor (Gram‐positive, anaerobic hyperthermophiles) are capable of deconstructing plant biomass without enzymatic or chemical pretreatment. Here, we show that co‐expression of the A. cellulolyticus Acel_0615 β‐glucanase (GH6 and GH12) and E1 endoglucanase (GH5) resulted in an increase in the activity of the exoproteome on Avicel; as well as an increase in growth of C. bescii on Avicel compared to the parental strain or the strain expressing the β‐glucanase alone.